The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41375-021-01469-x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling clonal hematopoiesis in umbilical cord blood cells by CRISPR/Cas9

Abstract: To investigate clonal hematopoiesis associated gene mutations in vitro and to unravel the direct impact on the human stem and progenitor cell (HSPC) compartment, we targeted healthy, young hematopoietic progenitor cells, derived from umbilical cord blood samples, with CRISPR/Cas9 technology. Site-specific mutations were introduced in defined regions of DNMT3A, TET2, and ASXL1 in CD34+ progenitor cells that were subsequently analyzed in short-term as well as long-term in vitro culture assays to assess self-rene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…The exact mechanisms by which some mutations promote a clonal advantage and accelerate atherosclerosis, for instance by provoking inflammation, remain to be elucidated. From what is known so far, CHIP mutations convey enhanced self-renewal of the hematopoietic stem cell (HSC) compartment and concomitantly obstructed hematopoietic differentiation in a mutation-specific fashion [ 24 , 25 , 47 ]. The most frequent mutations within TET2 and DNMT3A further promote granulomonocytic differentiation to the expense of the erythroid lineage [ 57 , 88 ].…”
Section: Cardio-oncology Axis: Future Perspectivesmentioning
confidence: 99%
“…The exact mechanisms by which some mutations promote a clonal advantage and accelerate atherosclerosis, for instance by provoking inflammation, remain to be elucidated. From what is known so far, CHIP mutations convey enhanced self-renewal of the hematopoietic stem cell (HSC) compartment and concomitantly obstructed hematopoietic differentiation in a mutation-specific fashion [ 24 , 25 , 47 ]. The most frequent mutations within TET2 and DNMT3A further promote granulomonocytic differentiation to the expense of the erythroid lineage [ 57 , 88 ].…”
Section: Cardio-oncology Axis: Future Perspectivesmentioning
confidence: 99%
“…Interestingly, a recent study showed an experimental approach based on CRISPR/Cas9 technology to develop a simple model of clonal hematopoiesis. 133 Site-specific mutations were introduced in specific sites of ASXL1, DNMT3A , and TET2 in CD34 + progenitors derived from umbilical cord blood. The biological effects induced by these genetic modifications were assayed in short-term and long-term cultures, evaluating changes in self-renewal and cell differentiation; TET2 , but not DNMT3A and ASXL1 mutations induced enhanced self-renewal in short-term cultures; all the three mutants and particularly the combined three mutants elicited a clear increase of self-renewal, as evidenced by long-term culture experiments.…”
Section: The Discovery Of Clonal Hematopoiesis Of Indeterminate Poten...mentioning
confidence: 99%
“… 133 In addition, the analysis of clonal expansion after long-term culture showed a mutation-specific impact on stem/progenitor cells. 133 …”
Section: The Discovery Of Clonal Hematopoiesis Of Indeterminate Poten...mentioning
confidence: 99%
See 2 more Smart Citations